Small-for-Gestational-Age Birth and Maternal Plasma Antioxidant Levels in Mid-Gestation: A Nested Case-Control Study. Issue 2 (June 2016) - Cohen, J.M.; Kahn, S.R.; Platt, R.W.; Basso, O.; Evans, R.W.; Kramer, M.S.
Abstract : ( BJOG. 2015;122:1313–1321) This is one of only a few prospective studies to assess antioxidant levels during pregnancy and the risk of small-for-gestational-age (SGA) birth. It includes the largest number of cases and most comprehensive set of antioxidants measured in studies published to date. The aim of the study was to prospectively measure a broad panel of maternal plasma antioxidant biomarker levels in mid-pregnancy and assess their association with the risk of SGA birth. It is hypothesized that higher levels of antioxidants in maternal blood may provide some protection from SGA birth.